OBJECTION TO GENERATIONAL RESEARCH IN COMMUNICATION STUDIES: A THEORETICAL CRITIQUE - Kaan Taşbaşı (Vivat Academia, 2023)
Introduction: In recent years, the characterization of the X/Y/Z generation has been used almost continuously in both popular thought and discourse and in academic literature. According to this conceptualization, generational difference is accepted as the primary determinant of social and political transformation. Theoretically and methodologically, studies that focus on the ways in which generations use communication technologies should be seen in relation to the American positivist research tradition that began and grew in the 1930s. The other pillar of these studies can be seen as based on the work of Marshall McLuhan, which came to the fore in the late 1950s. Another cornerstone of these studies should not be overlooked in relation to the arguments of postmodern theory, which proclaims the death of class, based on the assumption that it is not possible to perceive and change the world holistically in the 1960s. Methodology: This study presents a theoretical and methodological critique of studies that focus on the relationship between society/youth segments defined as Generation X/Y/Z and digital communication technologies. As a qualitative and explanatory research, this study has tried to prove that the dominant communication research/microscopic research, technological determinism, and postmodern theory are grounded on the same level. Results: The results of this study demonstrate that the characterization of the X/Y/Z generations as the primary determinants of social and political transformation should be viewed in the context of the American positivist research tradition, the work of Marshall McLuhan, and the arguments of postmodern theory. Furthermore, it is argued that these approaches share similar methodological and theoretical foundations in relation to communication research and digital communication technologies. Conclusions: In conclusion, this study highlights the importance of considering the historical and theoretical context in which the characterization of the X/Y/Z generations is situated. It is evident that the relationship between these generations and digital communication technologies is complex and cannot be understood solely through a deterministic lens. Moreover, the need for methodological critique in communication research to avoid oversimplifications and excessive generalizations is underscored. Ultimately, it is suggested that future research should take a more nuanced and contextualized perspective on the relationship between generations and communication technology.